2017
DOI: 10.1111/brv.12339
|View full text |Cite
|
Sign up to set email alerts
|

Beyond chemoreception: diverse tasks of soluble olfactory proteins in insects

Abstract: Odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) are regarded as carriers of pheromones and odorants in insect chemoreception. These proteins are typically located in antennae, mouth organs and other chemosensory structures; however, members of both classes of proteins have been detected recently in other parts of the body and various functions have been proposed. The best studied of these non-sensory tasks is performed in pheromone glands, where OBPs and CSPs solubilise hydrophobic semiochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
504
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(516 citation statements)
references
References 195 publications
(314 reference statements)
9
504
1
2
Order By: Relevance
“…The number of OBPs detected in B. tabaci (eight) is substantially lower than that detected in Drosophila melanogaster (52), Anopheles gambiae (69), Bombyx mori (44), Tribolium castaneum (50) and Apis mellifera (21) (Table S4) (Lynch & Conery, ; Zhou, ; Vieira & Rozas, ; Xue et al ., ; Benoit et al ., ; Mesquita et al ., ; Pelosi et al ., ). The relatively low number of OBPs in B. tabaci has several possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…The number of OBPs detected in B. tabaci (eight) is substantially lower than that detected in Drosophila melanogaster (52), Anopheles gambiae (69), Bombyx mori (44), Tribolium castaneum (50) and Apis mellifera (21) (Table S4) (Lynch & Conery, ; Zhou, ; Vieira & Rozas, ; Xue et al ., ; Benoit et al ., ; Mesquita et al ., ; Pelosi et al ., ). The relatively low number of OBPs in B. tabaci has several possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genome predicts 27 genes which encode OBPs (Mesquita et al, 2015), only 17 OBPs were found to be expressed in adult antennae (Oliveira et al, 2017), which suggests that several genes belonging to the OBP family may not be directly involved in odor transport, as observed in other insects (Pelosi et al, 2018). Moreover, amongst the 11 OBP transcripts identified in antenna, leg, proboscis, and head from adults ( Figure 1 ), four had already been described in the midgut transcriptome: RproOBP1 , RproOBP11 , RproOBP14 , and RproOBP24 (Ribeiro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…New cases due to vector transmission were estimated to 29,925/year (WHO, 2015). Several proteins participate in insect chemosensation, including odorant binding proteins (OBPs), which transports odor molecules through the sensillum lymph to odorant receptors (ORs) (Fan et al, 2011; Leal, 2012; Brito et al, 2016; Pelosi et al, 2018); ORs located in the membrane of olfactory sensorial neurons (Benton, 2006), which recognize volatile odorant molecules (de Bruyne and Baker, 2008); and ionotropic receptors (IRs), which detect diverse chemical ligands from the environment (Benton et al, 2009). OBPs represent the first contact between semiochemicals from the environment and the olfactory sensory system since they are responsible for transporting hydrophobic ligands to their specific ORs (Wojtasek and Leal, 1999; Fan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensitive and delicate olfactory system is vital for insects to communicate with their external environment, including host seeking, mating, and avoiding predators . Antennae are the major olfactory organ, with many hair‐like structures called sensilla.…”
Section: Introductionmentioning
confidence: 99%